Assessment of Obesity Frequency and Related Factors on Individuals Attending to the Department of Nutrition and Dietetics - Aliye Çayır; Nazlı Atak; Serdal Kenan Köse (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Objectives: This research was planned to assess the obesity and related factors on individuals ap-plying to the department of Nutrition and Dietetics, İbn-i Sina Training and Research Hospital, Medi-cal School, Ankara University. Study Design: This descriptive study was conducted on 450 people accepted to participated in the study. The data were collected by a questionnaire including 5 sections and 59 questions. In statisti-cal analyses, test of chi-square was used and p value below 0.05 was accepted to be statistically significant. Results: The obesity ratio was 28.0% and obesity was associated with some sociodemographic characteristics such as gender, age, marital status, educational level, and monthly income. Duration of marriage, number of children, obesity in childhood, having obesity treatment before, dieting for loosing weight and menoupose were indicated to influence the obesity. High obesity ratios in participants having family history of obesity, neglecting main and in-between meals were contributed that obesity was related to nutritional habits.Conclusion: In the development of obesity it is thought that multiple factors such as nutritional habits, life-style, age, gender, and sociodemographic characteristics are effective. Therefore, for the prevention and control the obesity, it is suggested to develop modifiable risk factor centered pre-ventive and interventional studies prioritizing individulas under high risks will be convenient.